Fast Oxygen Reduction Catalyzed by a Copper(II) Tris(2‐pyridylmethyl)amine Complex through a Stepwise Mechanism. (24th July 2019) - Langerman, Michiel; Hetterscheid, Dennis G. H.
Abstract: Catalytic pathways for the reduction of dioxygen can either lead to the formation of water or peroxide as the reaction product. We demonstrate that the electrocatalytic reduction of O2 by the pyridylalkylamine copper complex [Cu(tmpa)(L)] 2+ in a neutral aqueous solution follows a stepwise 4 e − /4 H + pathway, in which H2 O2 is formed as a detectable intermediate and subsequently reduced to H2 O in two separate catalytic reactions. These homogeneous catalytic reactions are shown to be first order in catalyst. Coordination of O2 to Cu I was found to be the rate‐determining step in the formation of the peroxide intermediate. Furthermore, electrochemical studies of the reaction kinetics revealed a high turnover frequency of 1.5×10 5  s −1, the highest reported for any molecular copper catalyst. Abstract : Schritt für Schritt : Der Mechanismus der elektrochemischen Reduktion von Disauerstoff durch einen einkernigen Pyridylalkylamin‐Kupfer‐Komplex wurde untersucht (siehe Bild). Es wurde gezeigt, dass in neutraler wässriger Lösung Disauerstoff eine schrittweise Reduktion eingeht, wobei Wasserstoffperoxid eine Schlüsselrolle spielt. Die bestimmten Geschwindigkeitskonstanten gehören zu den höchsten für molekulare Sauerstoff‐Reduktionskatalysatoren.